Functional Family Therapy (FFT) for Young People in Treatment for Non‐opioid Drug Use: A Systematic Review. Issue 1 (1st September 2015) - Filges, Trine; Andersen, Ditte; Jørgensen, Anne‐Marie Klint
Abstract : This Campbell systematic review assesses the effectiveness of FFT to reduce drug abuse (cannabis, amphetamines, ecstasy, or cocaine) among young people aged 11 to 21 years. The review includes two randomised controlled trials, but summarises findings from only one study reporting on the outcome of drug use. Two studies, reported in three papers, are included. Both were conducted in the USA. Only one provides outcomes related to youth drug use. It compares the effectiveness of FFT with that of alternative treatments. The results from the one study reporting on the effect of FFT on youth drug use shows a short‐term (four month) reduction in the use of cannabis, an effect that disappears in the longer term. There is a dearth of evidence on the effectiveness of FFT for the treatment of non‐opioid drug use in young people. Executive Summary/Abstract: BACKGROUND: Youth drug use is a severe problem worldwide. Usage of cannabis, amphetamine ecstasy and cocaine, referred to here as non‐opioid drugs, are strongly associated with a range of health and social problems. Functional Family Therapy (FFT) is a short‐term, manual‐based, behaviorally oriented family therapy program for young people with behavior problems such as drug abuse, juvenile delinquency and violence. Delivered in an outpatient setting, it aims to help young people and their families by improving family interactions and relationship functioning by addressing dysfunctional individual behavior. As with many other forms of family therapy, FFT targets young people and their families as a system. As such, it recognizes the important role of the family system in the development and treatment of young people's drug abuse problems. OBJECTIVES: The main aim of this review is to evaluate the current evidence on the effects of FFT on drug abuse reduction for young people in treatment for non‐opioid drug use. SEARCH METHODS: A wide range of electronic bibliographic databases were searched using a relatively narrow search strategy, in July 2013. We performed extensive searches in a broad selection of government and policy databanks, grey literature databases, citations in other reviews and included primary studies, and by hand searches of relevant journals and internet searches using Google. We also corresponded with researchers in the field of FFT. No language or date restrictions were applied to the searches. SELECTION CRITERIA: To be eligible for inclusion, studies must have: involved a manual‐based outpatient FFT treatment for young people aged 11‐21 years enrolled for non‐opioid drug use; used experimental, quasi‐experimental or non‐randomized controlled designs; reported at least one eligible outcome variable measuring abstinence, reduction of drug use, family functioning, education or vocational involvement, retention, risk behavior or other adverse effects; not focused exclusively on treating mental disorders; and had FFT as the primary intervention. DATA COLLECTION AND ANALYSIS: The literature search yielded a total of 6, 719 records, which were screened for eligibility based on title and abstract. From these, 108 potentially relevant records were retrieved and screened in full text, of which 9 records were potentially relevant. Finally, two studies based on three records were included in the review. Metaanalysis was not possible because only one study provided numerical results on the effect of FFT on drug use reduction. RESULTS: Two studies were included and both analyzed relative effects, comparing FFT to other interventions. Only one study provided numerical results on drug use reduction comparing FFT to two other interventions (CBT and a group intervention). The reported results indicate a positive effect favoring FFT on drug use frequency at 4‐month follow up, with no statistically significant difference at 7‐month follow up. AUTHORS' CONCLUSIONS: There is insufficient firm evidence to allow any conclusion to be drawn on the effect of FFT for young people in treatment for non‐opioid drug use. There is a need for more research, and particularly for more methodologically rigorous studies in the field of treatment for young drug users. The aim of this systematic review was to explore what is known about the effectiveness of FFT for the purpose of reducing youth drug use. The evidence found does not provide a basis for drawing conclusions about actual outcomes and impacts. Consequently, no substantive conclusion on the effectiveness can be made, neither supporting nor rejecting of the present FFT treatment approach.